An alternative technique for preparing monogeneans - Gallas, Moisés (2024)
Monogeneans encompass a group of parasites whose identification requires the visualization of both internal and external morphology. In most cases, the techniques involve many steps and the use of restricted substances, in addition to the necessity of protective equipment. Faure’s mounting medium, an aqueous medium similar to Hoyer’s mounting medium, has already been used for the preparation of the group. The aim of this study was to evaluate the effectiveness of Faure’s medium for the mounting of stained specimens. For this purpose, specimens of Microcotyle pomatomi Goto, 1900 and Gotocotyla acanthura (Parona & Perugia, 1896) Meserve, 1938, collected from Pomatomus saltatrix (Linnaeus, 1766) in the southernmost part of Brazil were used. The monogeneans were stained with five different dyes and mounted between a slide and coverslip using Faure’s mounting medium. The specimens that exhibited the best results were stained with Gomori’s trichrome and Semichon's acetic carmine. Monogeneans stained with eosin and fast green showed less satisfactory results, primarily because they did not highlight the structures of the reproductive systems. The analysis after years of preparation revealed that the characteristics and conditions of the staining and preparations remained in good condition, ensuring durability. The technique presented establishes a quick and effective method and provides an alternative for mounting monogeneans, especially when dealing with large infrapopulations.